Perceived Justice in Political Marketing: An Exploratory Study - Susila, Ihwan (UI Scholars Hub, 2021)
The purpose of this study is to criticize and develop the construct of equity theory within the framework of perceived justice. Specifically, this study aims to investigate perceived justice construct in political marketing perspective. Sample of the research consist of voters of political parties in Indonesia.Data were collected through interviews and a survey using a structured questionnaire with a purposive sampling method to 150 respondents. The study use exploratory factor analyses and Cronbach Alpha method to test the construct validity. The research also use measurement model of structural equation model (SEM) which is the same as confirmatory factor analysis procedure. Qualitative method also used in this research to investigate the new construct of perceived justice in political marketing. Result of the study found that procedural justice has weak construct validity and the definition of the construct is not clear. Findings the new concept of justice in a political marketing perspective discussed in this article.